A Java Based Web Service Model for Library Information Discovery - Nordin A Rahman, M; Hafizu Uba, Usman (International Journal of Engineering and Technology, 2018)
Library information discovery is a vital aspect of education development and management. Nowadays, many libraries offer the information regarding to facilities, resources and services to users through their website. The existing library information systems discover only their information and do not integrate the related information from other libraries. Therefore, web service technology has been developed, which is uses a standard interface to enable the consumer-to-business (C2B) or business-to-business (B2B) easily interact over the website. Currently, there is no standard model is developed to facilitate the users to discover and integrate the information of facilities, resources and services that published in the libraries website. This article discussed the development of a web service model that can discover and integrate the information in the various libraries website to the users by using Java Technology application program interface and tools provided by the integrated Web Services Stack. In the modelling process, the library websites are converted into Extensive Markup Language format (XML) for examining the Simple Object Access Protocol (SOAP) of each website. The converted XML files are stored as the application data source, which lies as the core of the web service model. By using an XML parser, the XML files are parsed into XMLDOM format for manipulating its contents. XML request object hypertext protocol is used to receive or reload the data from the client to the server. Finally, HTML and cascading style sheet (CSS) are used to reload the information to the client and display it. The results show that the proposed model is able to achieve over 90% of information discovery average precision performance regarding to user’s query on facilities, resources and services provided in the library websites. The developed model can benefit library’s users to extract the resources, facilities and services provided by the library intelligently.